Induction of an Embryonic Mouse Innate Immune Response following Inoculation In Utero with Minute Virus of Mice - Rostovsky, Irina (J Virol, 2014)
We used an embryonic-infection model system to show that MVMp, the prototypic minute virus of mice (MVM) serotype and a member of the genus Protoparvovirus, triggers a comprehensive innate immune response in the developing mouse embryo. Direct inoculation of the midtrimester embryo in utero with MVMp results in a widespread, productive infection. During a 96-h infection course, embryonic beta interferon (IFN-β) and IFN-γ transcription were induced 90- and 60-fold, respectively. IFN-β levels correlated with the embryo viral burden, while IFN-γ levels first increased and then decreased. Production of proinflammatory cytokines, interleukin 1β (IL-1β) and tumor necrosis factor alpha (TNF-α), also increased, but by smaller amounts, approximately 7-fold each. We observed increased levels of downstream antiviral effector molecules, PKR and phosphorylated STAT2. Finally, we showed that there is an immune cell response to the virus infection. Infected tissues in the embryo exhibited an increased density of mature leukocytes compared to the same tissues in uninfected embryos. The responses we observed were almost completely restricted to the infected embryos. Uninfected littermates routinely exhibited small increases in innate immune components that rarely reached statistical significance compared to negative controls. Similarly, the placentae of infected embryos did not show any significant increase in transcription of innate immune cytokines. Since the placenta has both embryonic and maternal components, we suggest there is minimal involvement of the dam in the response to infection. IMPORTANCE Interaction between the small single-stranded vertebrate DNA viruses, the protoparvoviruses, and the host innate immune system has been unclear. The issue is important practically given the potential use of these viruses as oncotherapeutic agents. The data reported here stand in contrast to studies of innate immune response during protoparvovirus infection of adult hosts, which invariably reported no or minimal and sporadic induction of an interferon response during infection. We conclude that under conditions of robust and productive MVM infection, a normal murine host is able to mount a significant and broad innate immune response.